Effects of complete mineral mixture and uréia on coastal bermudagrass hay (Cynodon dactylon (L.) pers.) cv. coast cross 1 - Zanetti, Marcus Antonio; Mellotti, Laercio; Filho, José Carlos Machado Nogueira; Feitosa, Adelma Santana Leal; Valvasori, Edson (Pesquisa Agropecuaria Brasileira, 1993)
Twenty castrated sheep were utilized in a digestibility and nitrogen balance trial conducted in the Department of Ruminant Breeding and Animal Nutrition of the Faculty of Vet-erinary Medicine and Zootechny of the University of São Paulo, Pirassununga Campus. The ob-jective of the experiment was to determine the positive effects of the addition of ureia in mineral mixture on the utilization of nutrients of bermudagrass hay. The animals were distributed into four treatments, following a factorial scheme, with two types of bermudagrass hay, supplemented or not with ureia incorporated into the complete mineral mixture. The medium digestibility coef-ficients were, for the control group and for the experimental group respectively, the following: dry matter, 49.8 and 47.8% protein, 57.6 and 63.7%: either extract, 36.2 and 33.9%; crude fiber, 55.7 and 51.9%; nitrogen free extracts, 53.0 and 47.3%. The control group presented a negative nitrogen balance of -21.3 g, and the experimental group, of -26.3 g. The sheep receiving the ureia during the 35-day period lost 49.8 g/day of live weight while sheep treated with ureia incorporated into the mineral salt lost only 1.1 g/day.